The Trends and Magnitude of Tree Plantation Growing in Rural Communities of Kigezi Sub-region, South Western Uganda - Tumushabe, Jennifer Turyatemba; Bariyomu, Rogers; Bwanika, Brain; Twongyirwe, Ronald (East African Nature and Science Organization, 2023)
The study documents the trends and magnitude of tree plantation growth in the Kigezi Sub-region of South Western Uganda. In most developing countries, national governments have been promoting and supporting rural communities with tree-planting programs in the region. A trend analysis was used to determine the escalating tree plantation growth in the sub-region. Landsat (TM/ETM+) satellite images were used to capture the trends, and a survey was also used to obtain information on the distribution patterns of established tree plantations. A randomly selected sample of 389 tree plantation growers was surveyed. The research approaches adopted were to supplement and strengthen the findings and also to provide an opportunity for the researcher to understand in-depth how tree plantations grow in the rural livelihood economy. Recommendations from this study emphasise the strengthening of the existing policy reforms. Also, interventions to harness sustainable forestry management should be used to provide integrated benefits to all, ranging from safeguarding local livelihoods to protecting the biodiversity and ecosystems provided by forests and reducing rural poverty in the Kigezi sub-region